Penyesuaian Diri Mahasiswa Calon Guru Biologi: Tinjauan pada Hasil Belajar Mata Kuliah Dasar: (Adjustment of Biology Teacher Candidates: A Review on the Learning Outcomes of Basic Courses) - Sugiyanto, Fadilah Nur; A N, Ayu Nabila; Widyadinata, Nanda (BIODIK, 2026)
The learning outcomes of basic courses contribute to the mastery of other courses. This study aims to analyze the adjustment of new students to academic and social transitions by reviewing the learning outcomes of the basic courses in General Chemistry and Biochemistry. The study employed a quantitative descriptive approach with a sample of 40 students from the Biology Education (Tadris Biologi) study program, Faculty of Tarbiyah and Teacher Training Sciences. The sample was selected using purposive sampling. The research instruments consisted of a questionnaire covering indicators of academic and social adjustment, as well as tests on the learning outcomes of basic courses. Data were analyzed to examine the relationship between the level of student adjustment and learning outcomes in the courses under review. The research results indicate that there is no significant relationship between students' adjustment to academic and social demands and their learning outcomes. This indicates that other factors play a role in affecting the learning outcomes of new students. Therefore, further and more in-depth research is needed to identify the contributing factors to learning outcomes so that comprehensive strategies for assisting new students can be designed. Abstrak. Hasil belajar mata kuliah dasar berkontribusi pada penguasaan mata kuliah lainnya. Penelitian ini bertujuan untuk menganalisis penyesuaian diri mahasiswa baru terhadap transisi akademik dan sosial dengan tinjauan pada hasil belajar mata kuliah dasar kimia dasar dan biokimia. Penelitian ini menggunakan pendekatan deskriptif kuantitatif dengan sampel penelitian sebanyak 40 mahasiswa program studi Tadris Biologi, Fakultas Ilmu Tarbiyah. Teknik pengambilan sampel penelitian dilakukan menggunakan purposive sampling. Instrumen penelitian meliputi angket yang memuat indikator penyesuaian diri aspek akademik & sosial serta tes hasil belajar mata kuliah dasar. Data dianalisis untuk melihat hubungan antara tingkat penyesuaian diri mahasiswa dengan hasil belajar pada mata kuliah yang ditinjau. Hasil penelitian menunjukkan bahwa tingkat persentase penyesuaian diri mahasiswa terhadap tuntutan akademik dan sosial belum tampak signifikan memengaruhi hasil belajar. Temuan ini mengindikasikan ada faktor lain yang berperan dalam memengaruhi hasil belajar mahasiswa baru. Dengan demikian diperlukan penelitian lebih lanjut dan mendalam untuk mengidentifikasi faktor-faktor yang memiliki kontribusi terhadap hasil belajar agar strategi pendampingan mahasiswa baru dapat dirancang secara komprehensif.